O Jogo e a teoria do processamento da informação no ensino de geometria molecular - Silva, Cleberson Souza da (2020)
This research developed and evaluated a game based on the Theory of Information Processing, particularly, on the Computational Theory of Mind with the objective of enabling the learning of concepts related to Molecular Geometry. The Theory of Information Processing is a descriptive model that explains how the human mind processes the information it receives, thus, the Computational Theory of Mind is a type of Theory of Information Processing that lists concepts such as symbol, input, output and processing for explain the processing of information in the mental structure of individuals. In this dissertation, based on the Computational Theory of Mind, a board and card game called: GeomeQuímica, which has in its scope themes such as: Molecular Geometry, Polarities of Molecules and Angle of Bond. The main idea of this dissertation was that from the elaborated game it was possible to provide an adequate process of construction of the knowledge of concepts related to Molecular Geometry. For this, this research was characterized as a qualitative case study. It is important to highlight that in a qualitative research, the researcher does not remain distant from his object of study, on the contrary, he is within the field of analysis trying to capture the meanings of the phenomena he is studying. Thus, the author of this dissertation, and a teacher at a public school of Basic Education located in the city of Luziânia in the state of Goiás in Brazil, invited his students from two classes of the first grade of High School to participate in the aforementioned game. In one class, students participated in the game from an application perspective in which it was considered Didactic and in the other as Pedagogical. Didactic Game is that game that the teacher usually uses to reinforce content that he has already taught. On the other hand, the Pedagogical Game is one that students participate before they have even studied about the subject addressed, in order to learn from the game. While the students participated in the game, their speeches were recorded using audio and video, and later transcribed and analyzed using the Content Analysis technique. The students' speeches generated the following five categories of analysis: Doubts involving the Operation and the Rules of the Game; Evaluation; Mathematical concepts; Chemical Concepts and Associative Networks. From these categories it was possible to perceive that during the game the students presented typical characteristics of the game as pleasure, fun and little competitiveness. We infer, through the analysis of the categories, that when the students participated in GeomeQuímica acting as Didactic Game, it managed to enable a greater learning of the concepts covered. On the other hand, GeomeQuímica acting as a Pedagogical Game was able to favor learning from error, which is often not done by schools. Thus, it was possible to approximate the most relevant concepts of the Computational Theory of Mind with the concepts of Piaget's Genetic Epistemology as: symbol corresponding to scheme; assimilation input; output the accommodation and processing the equilibration.